Application of immobilized enzymes in food technology industry / Siti Nadhirah Supardi and Hisham Mohd Nooh - Supardi, Siti Nadhirah; Mohd Nooh, Hisham (2021)
Enzymes found in living organisms accelerate a wide range of chemical and biological reactions. The lack of long-term working stability, shelf-life, and challenging recovery and reusability limit all of enzymes' promising applications in the food sector. The enzyme must be immobilized using an encapsulating technique to overcome this disadvantage. Carrier components for the encapsulation process, such as carbohydrates, protein, and lipid-based encapsulation, must be carefully chosen. Therefore, different support materials have varying degrees of influence on immobilized enzyme activity. Support materials for immobilizing enzymes must satisfy the enzymes' needs while also being sturdy enough to withstand the enzymatic processes' circumstances. The goals of this research are to discover new immobilized enzymes and to determine the role of immobilized enzymes in the baking, sugar, juice, and dairy industries. Furthermore, to investigate ways for improving immobilized enzymes by considering immobilization practice and carrier support. Additionally, to determine whether immobilized enzymes would affect the physical and chemical qualities of food, as well as to determine how many times immobilized enzymes have been utilized. The data revealed that different types of supports have a significant impact on the surrounding environment's hydrophilicity or hydrophobicity, altering whether chemicals partition towards or away from the enzyme. This approach is commonly used to stabilize enzymes in the presence of inactivating substances such as organic solvents, hydrogen peroxides, oxygen, and other dissolving gases. The carrier materials were identified to have biodegradability, biocompatibility, multivalent functionalization, good reusability, money savers, unique structural features, and remarkable stabilities. Carrier materials play an important role in enzyme immobilization. Consequently, higher scrutiny of enzyme catalytic performance on a commercial scale may be applied based on new matrices that could improve biocatalytic potentialities, novel enzyme immobilization methods, and advanced functional and innovative materials to fulfil expanding international needs.